Suction Cup on Denture: A Case Report - Pradyumna Ku Sahoo1, Smita R. Priyadarshini2, Kajal Kiran Sahu3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Complete Dentures with perfect retention are complicated to attain and several method have been appliedfor obtaining the same the same. Ill-fitting dentures are due to residual ridge resorption causing difficultywhile eating and even dislodgment during talking causing embarrassment for the patient. Suction cup waswidely used for retention & stability of dentures but is said to be associated with complications like palatalperforations and oro-antral communications. Here we present a case report of denture stomatitis & palatalperforation due to the suction cup.